Dinamika Psikologis pada Caregiver yang Memiliki Keluarga Penyandang Skizofrenia - Riana, Riska; Murdiana, Sitti (Universitas Pendidikan Muhammadiyah Sorong, 2023)
The psychiatric disorder schizophrenia has a big impact on caregivers. Caregivers as individuals who care for and accompany schizophrenia patients find many problems in carrying out their roles and responsibilities. This research aims to examine the dynamics experienced by caregivers in caring for schizophrenia patients. This research uses a qualitative method with a case study approach. The respondents in this study were two caregivers and two significant others who were obtained through purposive sampling techniques. Data collection techniques use interviews and documentation. The data obtained was then analyzed using data driven techniques. The results of data analysis produced two major themes, namely the psychological dynamics experienced by caregivers which include aspects of thoughts, emotions and behavior, as well as factors that influence caregivers to continue caring for schizophrenic patients. The results of this research can provide an overview of the condition of caregivers who care for schizophrenic patients who need support from both family and society.